Evaluation of Liraglutide Effect on Serum Adipocytokines of Adults Male Wistar Rats with Insulin Resistance That Induced by High Fat Diet - Furqan Mohammed Abdulellah; Mustafa Ghazi Al-abbassi; Dalia Abd alkader Shakur (College of Pharmacy / Mustansiriyah University, 2018)
Insulin resistance (IR) is the state in which insulin-stimulated glucose uptake is blunted in the insulin sensitive-tissue leading to state of prediabetes and T2DM, IR characterized by hyperglycemia and hyperinsulinemia in the fasting state, elevated glycosylated hemoglobin (HbA1c) level, hyperlipidemia, postprandial hyperglycemia, elevated plasma levels of pro-inflammatory markers and hypoadiponectinemia. Type 2 diabetes mellitus reported with peripheral insulin resistance (IR) and reduced production of insulin from pancreatic β-cells, IR elevates plasma fatty acids, decreasing glucose transportation to muscles and increased breakdown of fat finally leads to increased glucose production from the liver. This study was designed to evaluate the effect of liraglutide on serum adipocytokines of adult male rats with insulin resistance that induced by high fat diet, Chronic high fats diet feeding is a common cause of disturbing leptin signaling in hypothalamus leading to the state of hyperphagic obesity and leptin resistance. Liraglutide improve meal-stimulated insulin secretion so it's called incretin mimetic. It is glucagon like peptide-1 receptor agonist that adjust weight loss and glucose control via glucagon like peptide-1 receptors in the central nervous system or indirectly through activation of peripheral neurons. Current study utilized thirty-six adult male wistar rats (weighing 200-220gm), they were divided into two main groups: normal diet group (group A) that includes 12 rats receiving normal pellets and high fat diet group (group B and C) which has 24 rats feeding high fat diet pellets. Animals fed high fat diet pellets for 8 weeks to induce insulin resistance were divided into two groups: Group B received high fat diet pellets for 8 weeks then administered 0.5ml/kg normal saline intraperitoneal for four weeks. Group C received high fat diet pellets for 8 weeks then received 600μg/kg/day intraperitoneal liraglutide +0.5ml/kg normal saline four weeks along with high fat diet. High fat diet pellets caused a significant increase in body weight and blood glucose of high fat diet group. Liraglutide revealed a significant elevation in serum level of anti-inflammatory adipokines of group C. It also produces a significant reduction in serum level of pro-inflammatory cytokines of group C when compared with group B and control group. As conclusion, anti-inflammatory effects of liraglutide significantly elevate serum level of anti-inflammatory cytokines as well as significantly reduce serum level of pro-inflammatory cytokines.